No survival benefit with suboptimal CA19-9 response: defining effective neoadjuvant chemotherapy in resectable or borderline resectable pancreatic cancer. Issue 5 (May 2023) - Liu, Hao; D'Alesio, Mark; AlMasri, Samer; Hammad, Abdulrahman; Desilva, Annissa; Lebowitz, Steven; Rieser, Caroline; Ashwat, Eishan; Hampton, Erica; Khachfe, Hussein; Laffey, Mckenna; Singhi, Aatur; et al.
Abstract: Background/purpose: Neoadjuvant chemotherapy (NAC) is gaining popularity over a surgery-first (SF) approach in treating resectable and borderline resectable pancreatic ductal adenocarcinoma (PDAC). However, what constitutes effective neoadjuvant chemotherapy is unknown. Methods: We retrospectively analyzed resectable and borderline resectable PDAC patients who underwent pancreaticoduodenectomy (2010–2019) at a single institution. Optimal CA19-9 response was defined as normalization AND >50% reduction. We utilized Kaplan-Meier and multivariable-adjusted Cox models and competing risk subdistribution methods for statistical analysis. Results: 586 patients were included in this study. The multivariable-adjusted analysis demonstrated OS benefit in the NAC group only when OS was calculated from diagnosis (HR = 0.72, p = 0.02), but not from surgery (HR = 0.81, p = 0.1). However, in 59 patients who achieved optimal CA19-9 response, OS is significantly longer than the 134 patients with suboptimal CA19-9 response (39.3 m vs. 21.5 m, p = 0.005) or the 117 SF patients (39.3 m vs. 19.5 m, p < 0.001). Notably, a suboptimal CA19-9 response conferred no OS advantage compared to SF patients. The accumulative incidence of liver metastases (but not other metastases) was significantly reduced only in patients with optimal CA19-9 response to NAC (multivariable-adjusted subdistribution HR = 0.26, p = 0.03). Conclusion: CA19-9 response to NAC may serve as the marker for effective NAC. These findings warrant validation in a multi-institutional study.